Essential tuberculosis medicines and health outcomes in countries with a national essential medicines list. (May 2022) - Maraj, Darshanand; Steiner, Liane; Persaud, Nav
Abstract: Background: Tuberculosis (TB) remains a major cause of morbidity and mortality globally despite effective treatments. Along with high-quality health services, essential medicines are a key tool in curbing TB related mortality. Examining relationships between listing TB medicines on national essential medicines lists (NEMLs) and population health outcomes related to amenable mortality is one way to assess TB care. Methods: In this cross-sectional study of 137 countries, we used linear regression to examine the relationship between the number of TB medicines listed on NEMLs and TB related mortality while controlling for country income, region and TB burden. Results: Most countries listed essential TB medicines to treat latent, drug-sensitive and disseminated TB but few listed enough for multi-drug resistant TB (MDR-TB) therapy. The total number of TB medicines listed ranged from 1 to 29 (median: 19, interquartile range: 15 to 22). Over 75% of the variation in health outcomes were explained by the number of TB medicines listed, gross domestic product (GDP) per capita, region and high-burden MDR-TB status. The number of TB medicines listed was not associated with TB mortality. Conclusion: Most countries list essential TB treatments and the variation in TB outcomes is explained by other factors such as GDP.